Dietary Practice and Nutritional Status of Tuberculosis Patients in Pokhara: A Cross Sectional Study - Gurung, Lal M.; Bhatt, Laxman D.; Karmacharya, Isha; Yadav, Dipendra K. (Frontiers in Nutrition, 2018)
Background: Under nutrition increases the risk of progression from Tuberculosis (TB) infection to active TB disease and further leads to weight loss. Proper diet and nutrition play significant role to the TB patients. Active TB need high energy requirement. The main aim of this study is to assess the dietary intake and nutritional status of TB patients in Pokhara city of Nepal. Methods: A cross sectional descriptive study was carried out among 133 TB patients taking anti-tubercular drug. Data were collected using sequential sampling method. Data were collected from 4th October to 7th November, 2016. Results: This study revealed that about one-fifth of TB patients did not consumed sufficient amount of calorie as per RDA. More than one third patients were underweight during the time of registration and underweight is reduced to 21.6 percent in the present situation. Mean BMI was 20.99 kg/m2 (SD±5.81). Similarly, mean BMI among PTB is 19.82kg/m2 and 22.52kg/m2 in Extra PTB. Working condition and food intake frequency was significantly associated with calorie intake. This study found that amount of calorie, food frequency per day, types of TB and nutritional status during registration was found to be associated with recent nutritional status. There was significant difference between mean weight and BMI between at the time of registration and recent BMI and weight. Conclusion: Nutritional status has improved comparatively from the time of registration to the time of study. Proper nutritional counseling should be given to TB patients along with nutritional support to severely malnourished patients. Nutritional assessment of TB patients should be done periodically. Keywords: tuberculosis, nutrition, diet, TB patients, Nepal